2012
DOI: 10.3109/0886022x.2012.718711
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transdifferentiation of Renal Tubular Epithelial Cell Mediated by Oxidative Stress and Intervention Effect of Probucol in Diabetic Nephropathy Rats

Abstract: Objective: To elucidate the relationship of oxidative stress and specificity protein 1 (Sp1) in the process of epithelial-tomesenchymal transdifferentiation (EMT) and also to investigate the molecular mechanism of protective effect of probucol on the pathogenesis of diabetic kidney disease (DKD). Methods: Thirty male Sprague-Dawley (SD) rats were randomly divided into control group, diabetic group, and diabetic group under probucol therapy (n ¼ 10 per group). The biochemical indicators including 24-h urinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…We therefore surmised that probucol reduces oxidative damage by inhibiting p66Shc expression. Our results also support the findings of previous studies, which suggest that probucol is a cholesterol-lowering drug with antioxidant properties that protect against free radical-induced damage in a wide variety of scenarios, including doxorubicin-induced cardiotoxicity [7], HG-induced podocyte injury [49] and tubular epithelial cell injury [6]. The mechanism by which probucol protects against oxidative injury may involve increase in antioxidant gene mRNA expression and decrease in apoptosis via improving mitochondrial oxidative phosphorylation and energy production [1].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We therefore surmised that probucol reduces oxidative damage by inhibiting p66Shc expression. Our results also support the findings of previous studies, which suggest that probucol is a cholesterol-lowering drug with antioxidant properties that protect against free radical-induced damage in a wide variety of scenarios, including doxorubicin-induced cardiotoxicity [7], HG-induced podocyte injury [49] and tubular epithelial cell injury [6]. The mechanism by which probucol protects against oxidative injury may involve increase in antioxidant gene mRNA expression and decrease in apoptosis via improving mitochondrial oxidative phosphorylation and energy production [1].…”
Section: Discussionsupporting
confidence: 90%
“…Along these lines it has been demonstrated that probucol suppresses oxidative stress and attenuates oxidative injury in the renal podocytes of db/db mice by inhibiting NADPH oxidase 2 (Nox2) expression [49]. Conceivably, by virtue of probucol being an antioxidant it has been proposed to inhibit renal tubular epithelial- mesenchymal transition (EMT) in mouse models of DN [6], [31]. However, the molecular mechanism(s) underlying this phenomena are not precisely delineated.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, both mRNA and protein levels of α ‐SMA were increased in Group II compared with Group I. Probucol treatment markedly reduced α ‐SMA expression in rats treated with ethanol + CCl 4 . Interestingly, probucol has also been reported to reduce the upregulation of α ‐SMA in diabetic nephropathy rats . These results indicate that probucol protects against liver fibrosis at least in part by inhibiting HSC activation.…”
Section: Discussionmentioning
confidence: 82%
“…13 Renal tubular epithelial-myofibroblast transdifferentiation plays a very important role in the development of tubular lesion and tubulointerstitial fibrosis. 14,15 In the diabetic kidney, the extensive infiltration of monocytes/macrophages can cause the accumulation of extracellular matrix, thickening of the glomerular basement membrane, and the subsequent development of interstitial fibrosis and glomerular sclerosis. 16 Studies have shown that diffuse glomerulosclerosis is associated with macrophages infiltration.…”
Section: Discussionmentioning
confidence: 99%